2014
DOI: 10.1039/c4dt02299h
|View full text |Cite
|
Sign up to set email alerts
|

Gold(i) thiolates containing amino acid moieties. Cytotoxicity and structure–activity relationship studies

Abstract: Several gold(I) complexes containing a thiolate ligand functionalised with several amino acid or peptide moieties of the type [Au(SPyCOR)(PPh2R')] (where R = OH, amino acid or dipeptide and R' = Ph or Py) were prepared. These thiolate gold complexes bearing biological molecules possess potential use as antitumor agents. Cytotoxicity assays in different tumour cell lines such as A549 (lung carcinoma), Jurkat (T-cell leukaemia) and MiaPaca2 (pancreatic carcinoma) revealed that the complexes exhibit good antiprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…Diverse studies indicate that in gold(I) complexes with thiolates and phosphines as ligands the cytotoxicity is due mainly to the metallic centre; whereas the phosphine ligand allows the gold(I) atom to cross the cell membrane, the thiolate takes part in exchange ligand reactions with other biomolecules. Keeping this in mind, it is logical to think that adding more gold(I) atoms per molecule will increase the cytotoxicity of the complex, as we observed previously 18b. Moreover, there is a strong interest in the synthesis of lipophilic and cationic compounds which seem to be able to cross cell membranes and selectively accumulate in mitochondria,25 just where it appears that gold(I) complexes exert their therapeutic effect, by inhibiting diverse enzymes as for example thioredoxin reductase (TrX).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Diverse studies indicate that in gold(I) complexes with thiolates and phosphines as ligands the cytotoxicity is due mainly to the metallic centre; whereas the phosphine ligand allows the gold(I) atom to cross the cell membrane, the thiolate takes part in exchange ligand reactions with other biomolecules. Keeping this in mind, it is logical to think that adding more gold(I) atoms per molecule will increase the cytotoxicity of the complex, as we observed previously 18b. Moreover, there is a strong interest in the synthesis of lipophilic and cationic compounds which seem to be able to cross cell membranes and selectively accumulate in mitochondria,25 just where it appears that gold(I) complexes exert their therapeutic effect, by inhibiting diverse enzymes as for example thioredoxin reductase (TrX).…”
Section: Resultsmentioning
confidence: 66%
“…The type of amino acid ester has influence in the ability of the carrier to deliver the gold(I) to its target. In fact, in a previous work we observed that functionalisation with proline usually gives better cytotoxic complexes compared with other amino acids 18b. In this case, we decided to couple to the cystine derivative the octahydroindole amino acid ester (Oic), a non‐proteinogenic bicyclic proline analogue 24.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a number of gold conjugates derived from amino acids or peptides have been reported. As examples, N‐heterocyclic carbene (NHC)–gold complexes,, conjugates of ferrocene coordinated to gold(I) derivatives, gold(III) dithiocarbamates,, gold(I) azides, and gold(I) thiolates, with only one example of a chloro–gold–phosphane found in the recent literature.…”
Section: Introductionmentioning
confidence: 99%
“…The crystalline structures of the two alkylated PTA species [PTA-CH 2 -p-COOH-C 6 H 4 ]Br (1a) and [PTA-CH 2p-CH 2 COOH-C 6 H 4 ]Br (2) reveal the presence of interactions between the bromide anion and the OH group of the acid moiety. Bis-phosphane derivatives were prepared by the alkylation of two PTA molecules with a dibromide salt to afford more water- [a] olates [40,41] with only one example of a chloro-gold-phosphane [42] found in the recent literature.With this background, we describe herein the synthesis and characterization of new functionalized PTA molecules and the first amino acid-PTA conjugate as well as their coordination to gold(I) derivatives. Additionally, the results of a preliminary study of the cytotoxicity of these new gold complexes against colon cancer cell lines and differentiated cells (non-carcinogenic) are reported.…”
mentioning
confidence: 99%
“…A549 (lung carcinoma), Jurkat(T-cell leukaemia) and MiaPaca2 (pancreatic carcinoma) cytotoxicity assays demonstrate that the complexes can inhibit proliferation of tumor cells, with IC 50 values as low as in the micromolar range. They also conducted similar assays with several structural modifications in order to establish the structure-activity relationship in this family of complexes, facilitating to the design of new and more potent cytotoxic complexes [10]. Subsequently, they found that Au(I) complexes bearing cysteineinvolving dipeptides exhibited high cytotoxicity, showing a very low IC 50 values [11].…”
Section: Anticancer Study Of Au(i) Complexesmentioning
confidence: 99%